The virtues of underwear modesty, flamboyance and filth - Edwards, Nina (Reaktion Books, 2024)
"Stories are woven into the fabric of our most personal garments. From the first loincloths to the intricate layers of shapewear, the concealed world of underwear is capable of expressing individual desire and also aspects of society at large. An indicator of the vagaries of fashion, underwear can be simple or elaborate. It both safeguards and exposes, reflecting our hopes and experiences. Underwear can embarrass and excite, amuse and shame us. This book illuminates the sometimes profound significance of the garments we wear beneath our outer clothing. It discusses the history of both women’s and men’s underwear, and global cultures of dress" --
Keywords: Geschichte; Unterwäsche; Underwear / History; Sous-vêtements / Histoire